Biological Psychology / An Integrative Approach - Toates Frederick (Prentice Hall, 2001)
A comprehensive and engaging introduction to the biological bases of experience and behavior. Introduction, Integrating Explanations, Coordinated Action: Integrating Systems, Neurons: A Closer Look, The Brain: Basics of Structure and Role, Development, Sensory Systems: General Principles, Vision, The Other Sensory Systems, The Control of Movement, Learning and Memory, Firm Reflexes to Goals, Emotion, Stress and Coping, Pain, Motivation, Feeding and Drinking, Sexual Behavior, Psychoactive Drugs, Sleep and Walking, Cognition, Brains and Minds and Consciousness, Integration: Understanding How Things Can Go Wrong.